ESPACIALIZAÇÃO DA PRODUÇÃO DE Pinus taeda POR SORTIMENTO DE MADEIRA - SPONHOLZ, ISAAC KISZKA (2012)
This study presents an alternative to the spatial data simulation of forest production by assortment of wood, to assist in administrative and decision-making in the forestry company. For this study was used as a geographic information system for the System Georeferenced Information Processing - SPRING - and open source, developed by the National Institute for Space Research - INPE and the simulation of production was used Prognosis System for Growth and Production Plantations of Pinus - SISPINUS - developed by the Brazilian Agricultural Research Corporation - EMBRAPA. The integration with the SPRING SISPINUS allowed the spatial data and prognosis of growth in output per assortment of wood, a forest company by the year 2030, besides the possibility of spatial planning and programming of the rotation plots. The implemented system had enough practicality, providing rapid visualization of spatial information on production by assortment of wood, in addition to providing information about controlling the turnover of production plots and farms in business. The system allowed operational agility of information and can be applied both as administrative support in the planning of forestry companies.